WAYS TO PROMOTE DIGITAL TRANSFORMATION IN BEEKEEPING - Farmanov, Djonibek (THE INNOVATION ECONOMY, 2024)
The article describes the organizational and economic levers for promoting the transformation of digital technologies in the beekeeping industry. Proposals for subsidizing the implementation of digital technologies in the network are described. Also, in order to support structures that finance the implementation of digital technologies, the organization of the “Technological Transfer in Beekeeping” fund and the sources of its financing are disclosed